2020
DOI: 10.1007/s00404-020-05744-7
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell transfusion in obstetrics and its implication for patient blood management: a retrospective analysis in Switzerland from 1998 to 2016

Abstract: Purpose Peripartum hemorrhage (PPH) remains one of the main causes of maternal mortality worldwide. Treatment includes administration of packed red blood cells (RBC) in severe cases and patient blood management (PBM) may reduce it significantly. In our study, we wanted to retrospectively assess red blood cell administration in PPH to evaluate the impact of PBM in Switzerland. Methods Using data from the Swiss obstetric hospital registry (Arbeitsgemeinschaft Schweizer Frauenkliniken, ASF), we included patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Anemia during pregnancy is defined as the hemoglobin value below 11 g/dL in each trimester, according to the World Health Organization (WHO) [15]. Anemia is an important risk factor in postpartum bleeding [3]. This suggest that it is associated with unfollowed pregnancies that do not attend pregnancy follow-ups and do not use iron supplements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anemia during pregnancy is defined as the hemoglobin value below 11 g/dL in each trimester, according to the World Health Organization (WHO) [15]. Anemia is an important risk factor in postpartum bleeding [3]. This suggest that it is associated with unfollowed pregnancies that do not attend pregnancy follow-ups and do not use iron supplements.…”
Section: Discussionmentioning
confidence: 99%
“…This suggest that it is associated with unfollowed pregnancies that do not attend pregnancy follow-ups and do not use iron supplements. Current Swiss guidelines recommend that hemoglobin levels should be screened regularly at least once every trimester, and iron levels should be screened in the first trimester [3]. Various algorithms have been emphasized in postpartum hemorrhage, especially in massive bleeding, although the benefits of fibrinogen and tranexamic acid are shown, more studies are needed [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood transfusion is the most common method for the clinical treatment of patients with obstetric hemorrhage. It effectively solve the patient's anemia caused by excessive blood loss, helps maintain blood volume and blood pressure, exerts a certain preventive effect on patients with shock, and improves the prognosis of patients (11,12). However, a large number of clinical practices have found that after patients with obstetric hemorrhage receive a large transfusion of blood, although their life and safety are guaranteed, they also experience certain side effects, mainly manifested as abnormal blood coagulation (13).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also noted by Zdanowicz et al, which showed that RBC transfusion was more frequent in instrumental assisted delivery than Caesarean section or SVD. 26 The requirement for RBC transfusion in instrumental assisted delivery may be attributed to complications of these procedures such as perineal or cervical tear. 27 The obstetrics procedure with protective findings to the RBC transfusion in our study was Caesarean section; those who underwent this procedure had a 62.3% less chance to receive RBC transfusion than those who underwent normal SVD.…”
Section: Table Iii: Final Regression Model Of Factors Associated With Rbc Transfusion Among Obstetrics Patientsmentioning
confidence: 99%